2019
DOI: 10.1177/2372732219857750
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Aided Interventions for Individuals With Autism: Implications for Policy and Practice

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by pervasive difficulties in reciprocal social-communication skills and restricted, repetitive interests and behaviors. Advances in assistive technology can potentially improve the functional capabilities of individuals with ASD. This article reviews current legislation and professional standards related to educating students with ASD with an emphasis on technology and evidence-based practices. In particular, the article summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…There was a relative lack of technology-mediated studies focused on social communication interventions, play, or adaptive skills, all of which may benefit from technology (e.g., Saleh et al, 2021 ; Schmidt & Glaser, 2021 ). In a systematic review specific to ASD, authors found potential merits of using technology to support social communication deficits inherent to the ASD diagnosis (Pham et al, 2019 ). As more children have ready access to tablets, smart phones, and gaming platforms at home from a young age, interventions to support social communication capitalizing on the reinforcing nature of these technologies may be especially useful.…”
Section: Discussionmentioning
confidence: 99%
“…There was a relative lack of technology-mediated studies focused on social communication interventions, play, or adaptive skills, all of which may benefit from technology (e.g., Saleh et al, 2021 ; Schmidt & Glaser, 2021 ). In a systematic review specific to ASD, authors found potential merits of using technology to support social communication deficits inherent to the ASD diagnosis (Pham et al, 2019 ). As more children have ready access to tablets, smart phones, and gaming platforms at home from a young age, interventions to support social communication capitalizing on the reinforcing nature of these technologies may be especially useful.…”
Section: Discussionmentioning
confidence: 99%
“…Parents can seek information on potential treatments from a diversity of sources such as health professionals, books, newspapers, other parents, and the internet (Miller et al, 2012). Advances in technology and increased accessibility to the internet make the latter an important source of knowledge acquisition for parents of children with ASD (e.g., Grant et al, 2016;Hall et al, 2016;Pham et al, 2019). While Gibson et al (2017) found that parents prefer obtaining information relating to ASD from local resources (e.g., pediatricians, teachers, and local organizations), results from other studies have suggested that the internet is increasingly used as parents' primary source of information (Grant et al, 2016;Hall et al, 2016).…”
Section: Accuracy and Tone Of Posts In An Internet Forum On Autismmentioning
confidence: 99%
“…Finally, as technology continues to advance, becomes more portable, and begins to simulate reality (e.g., portable devices used in virtual reality simulations), the integration of VP tactics with this technology becomes possible. However, research into how such technology affects individuals with ASD, the practicality of using such technology in home and community settings, and the feasibility of integrating the instructional strategies with advance technology is needed (Pham et al 2019).…”
Section: Future Directionsmentioning
confidence: 99%